Réponses

  • Omnes
  • Modérateur confirmé
2014-03-27T17:17:16+01:00
Salut,

A= 9(-x+1)²-4(2x-3)²

Développement :

A= 9(-x+1)²-4(2x-3)²
A =9(x² -2x + 1) - 4(4x² -12x + 9)
A = 9x² - 18x + 9 - (16x² - 48x + 36)
A = 9x² - 18x + 9 - 16x² + 48x - 36
A = -7x² - 30x - 27

Factorisation :


A= 9(-x+1)²-4(2x-3)² -> A = a² -b², avec a = 3(-x+1) et b = 2(2x-3) -> a² - b² = (a-b)(a+b)
A = [3(-x+1) - (2(2x-3))][3(-x+1) + 2(2x-3)]
A = (-3x + 3 - (4x -6)][-3x + 3 + 4x - 6]
A = (-3x - 4x + 3 + 6)(x -3)
A = (-7x + 9)(x-3)

Bonne soirée !